World Economy Winter 2020 - Global economic recovery progresses overall - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2020)
In the third quarter of 2020, the global economy rebounded strongly from the steep fall in output suffered in the first half of the year amid the covid-19 pandemic. Currently, the recovery is being slowed down by another wave of infections and policy measures to contain it, but on aggregate global economy is likely remain on an upward trajectory. While GDP in Europe is likely to decline again in the fourth quarter, output should continue to rise in most of the rest of the world, with economic momentum in China being actually quite high. Unlike in spring, manufacturing output, international trade in goods, and raw material prices have apparently been hardly affected so far. Economic activity is likely to recover in the course of the first quarter even where it is currently depressed, as the wave of infection is expected to subside. In the remainder of the year, with the population increasingly being vaccinated, a progressive normalization of the economic environment can be expected, including for the particularly contact-intensive sectors of the economy. We have reduced our forecast for global growth from September by 0.2 percentage points for 2020 and by 0.6 percentage points for 2021. We now expect world output (measured on a purchasing power parity basis) to increase by 6.1 percent in 2021, following a 3.8 percent dropp in the current year. In 2022, global economic activity is projected to increase by 4.5 percent. While this is again stronger than the medium-term trend, production will nevertheless remain well below the level that had been expected before the crisis. For world trade in goods, we expect an increase of 8.8 percent, following a decline of 5.4 percent this year.
Keywords: 330; World Economy; advanced economies; emerging economies; monetary policy; Japan; Russia; ASEAN; Covid-19; COVOD-19; COVID19